資訊價值的時代意義 Exploring the Contemporary Meaning of Information Values - Chaoyun Chaucer Liang; Tzu-chiang Chang (Jiàoyù zīliào yǔ túshūguǎn xué, 1995)
無 Everybody is consuming information everyday, but the value of information we consumed has been ambiguous. Information value could be the profit gained from a business activity. It also could be the public welfare which advance the human society. This paper is aimed at exploring the contemporary meaning of information value. The authors first offer an operational definition for the term Information Value. Next, the cost and benefit resulted from this value are examined. The authors then provide three perspectives on information value in the modern economical environment. Finally, the authors wrap up this paper with an exploration of possible future- information as a public utility.